Review of laboratory‐based terrestrial bioaccumulation assessment approaches for organic chemicals: Current status and future possibilities. (12th October 2015) - Hoke, Robert; Huggett, Duane; Brasfield, Sandra; Brown, Becky; Embry, Michelle; Fairbrother, Anne; Kivi, Michelle; Paumen, Miriam Leon; Prosser, Ryan; Salvito, Dan; Scroggins, Rick
ABSTRACT: In the last decade, interest has been renewed in approaches for the assessment of the bioaccumulation potential of chemicals, principally driven by the need to evaluate large numbers of chemicals as part of new chemical legislation, while reducing vertebrate test organism use called for in animal welfare legislation. This renewed interest has inspired research activities and advances in bioaccumulation science for neutral organic chemicals in aquatic environments. In January 2013, ILSI Health and Environmental Sciences Institute convened experts to identify the state of the science and existing shortcomings in terrestrial bioaccumulation assessment of neutral organic chemicals. Potential modifications to existing laboratory methods were identified, including areas in which new laboratory approaches or test methods could be developed to address terrestrial bioaccumulation. The utility of "non‐ecotoxicity" data (e.g., mammalian laboratory data) was also discussed. The highlights of the workshop discussions are presented along with potential modifications in laboratory approaches and new test guidelines that could be used for assessing the bioaccumulation of chemicals in terrestrial organisms. Integr Environ Assess Manag 2016;12:109–122. © 2015 SETAC Key Points: Data and information on bioaccumulation of organic chemicals in terrestrial organisms, including plants, is often not considered or plays a minor role in current bioaccumulation assessments. Development of integrated assessment approaches that maximize and expand the use of laboratory toxicity data collected during regulatory testing is important to meet animal welfare concerns. Adaptation of available laboratory tests with terrestrial organisms (e.g., plants, invertebrates, and vertebrates such as birds, mice, rats, etc.) may provide data relevant for terrestrial bioaccumulation assessments. Relevant and meaningful metrics and a tiered framework for the expression and evaluation of the potential for bioaccumulation in terrestrial organisms and food chains need to be developed and agreed upon by the scientific and regulatory communities.